The Influence of Work Ability and Work Environment on Employee Performance at UPTD. Plut Small and Medium Business Cooperative Office af North Sumatra Province - Tanti Indrianty; Muhamad Toyib Daulay; Desi Astuti (Cattleya Darmaya Fortuna, 2026)
Employee performance is an important factor in achieving organizational goals, but there is still a decline in performance in UPTD. PLUT of the North Sumatra Province Small and Medium Business Cooperative Office which is allegedly influenced by Work Ability and Work Environment. This study aims to analyze the influence of work ability and work environment on employee performance. The research uses a quantitative method with an associative approach. The research population amounted to 41 employees and all of them were sampled through saturated sampling techniques. Data was collected through questionnaires, interviews, and documentation, then analyzed using multiple linear regression. The results of the study showed that work ability had a positive and significant effect on employee performance with a t-value of 7.551 and a significance level below 0.05. The work environment also has a positive and significant effect on employee performance with a t-value of 4.196 and a significance level below 0.05. Simultaneously, work ability and work environment had a positive and significant effect on employee performance with an F value of 35.823 and a significance level below 0.05 and an R-Square of 0.653. This study concludes that improving work ability and improving the work environment can improve employee performance. These findings have implications for the importance of training, competency development, and the provision of a comfortable work environment that supports optimizing employee performance.